2022
DOI: 10.1177/1420326x221084869
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the infection probability distribution of airborne and droplet transmissions

Abstract: Herein, a method is proposed to predict the infection probability distribution rather than the room-averaged value. The infection probability is predicted by considering both airborne and droplet transmissions based on CO2 concentration and the position of the occupants in a room. The proposed method was used in an actual office setting, and the results confirmed that it could provide a quantitative prediction of the infection probability by integrating the ventilation efficiency and the distance between occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Yamamoto et al proposed a probabilistic mathematical model for the distribution of airborne and droplets to predict Covid-19 infection [ 22 ]. For the parameters needed they relied on known estimation methods, however no real measurement or images processing was performed.…”
Section: Related Workmentioning
confidence: 99%
“…Yamamoto et al proposed a probabilistic mathematical model for the distribution of airborne and droplets to predict Covid-19 infection [ 22 ]. For the parameters needed they relied on known estimation methods, however no real measurement or images processing was performed.…”
Section: Related Workmentioning
confidence: 99%
“…9,10 Reasonable design of the location of air supply and exhaust outlets can optimize airflow distribution, which contributes to reducing the concentration of indoor contaminants. [11][12][13] Liu et al 14 studied the spatial and temporal distribution of bioaerosol particles under different mixed ventilation modes. They found that the removal efficiency of aerosol particles would be greatly improved if a directional airflow from the supply air inlet to the release source and then to the exhaust outlet could be formed in the ward.…”
Section: Introductionmentioning
confidence: 99%